2017
DOI: 10.14716/ijtech.v8i8.679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Absorbent Flow Rate on Co2 Absorption through a Super Hydrophobic Hollow Fiber Membrane Contactor

Abstract: The aim of this study is to evaluate the effects of absorbent flow rate on CO 2 absorption through a super hydrophobic hollow fiber contactor. The absorbent used in this study was a physical absorbent, namely a polyethyleneglycol-300 (PEG-300) solution. Meanwhile, the feed gases used in the experiments were pure CO 2 and a mixture of 30% CO 2 and 70% CH 4 . Gas absorption using a physical absorbent provides various benefits; for example, it can produce sufficiently high selectivity towards CO 2 and it is less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…This property allows adsorbents to absorb oil without absorbing water. Besides its use for oil-water separation, the hydrophobic membrane is also applicable for other separation systems (Kartohardjono et al, 2017;Kartohardjono et al, 2019). Recently, it was found that hydrophobic properties can be formed using chemicals by means of surface modification of adsorbents with hydrophobic material such as organosilanes, thus forming hydrophobic films.…”
Section: Introductionmentioning
confidence: 99%
“…This property allows adsorbents to absorb oil without absorbing water. Besides its use for oil-water separation, the hydrophobic membrane is also applicable for other separation systems (Kartohardjono et al, 2017;Kartohardjono et al, 2019). Recently, it was found that hydrophobic properties can be formed using chemicals by means of surface modification of adsorbents with hydrophobic material such as organosilanes, thus forming hydrophobic films.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption method, which is part of the carbon capture and storage (CCS) technology, is considered an efficient and economical method for replacing conventional technology in the CO2 scrubbing process, since the technology of amine solvents is deficient in corrosion and toxicity (Kartohardjono et al, 2017;Kusrini et al, 2018). Moreover, large amounts of energy are required to recycle amines, which diminishes the efficiency of energy usage, creates high costs in power plants, and produces corrosion in the pipeline (Ye et al, 2013;Mutyala et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sour gas which contains high CO 2 component is mostly removed from the gas stream utilizing acid gas removal unit (AGRU). The membrane-based gas liquid contactor recently also studied as the alternative technology for removing CO 2 from natural gas [2]. AGRU also used in coal gasification process to capture CO 2 [3].…”
Section: Introductionmentioning
confidence: 99%